HOW TO PROVOKE A CHILD TO ACQUIRE NEW KNOWLEDGE? (Conferencea, 2023)
The article talks about some factors affecting the learning process. The author informs us of his opinion on how to concentrate the student's attention on the educational issue; Some samples from own practice are given